Loneliness Among Inspired Citizens by the Class IIb Women's Penitentiary in Kupang City - Say, Maria Halena Soka; Manafe, Rizky Pradita; Mage, Mernon Yerlinda Carlista (Journal of Health and Behavioral Science, 2024)
Criminal acts in Indonesia have increased. These acts are triggered by social and emotional factors that make someone designated as a prisoner. Being in prison triggers feelings of loneliness, which is an emotional and cognitive response to the situation of someone who has few social relationships because they do not match what they want. Loneliness is caused by a lack of support, personality, relationships and isolation of the inmates, and this has an impact on the level of loneliness. This research aims to determine the level of loneliness among inmates at the Class IIb Women's Penitentiary in Kupang City. The type of research is descriptive quantitative. Participants in the research were 48 participants. The research results show that loneliness is in the high category at 48%. Loneliness aspect scores viz Social Desirability 52% is in the high category. The research results are expected the Class IIb Women's Penitentiary in Kupang City can maximize programs already running by building innovations in each program to reduce loneliness among inmates.